Benzimidazole‐1, 3, 4‐Oxadiazole Hybrids: Synthesis, Anticancer Evaluation, Docking and DFT Studies. Issue 36 (21st September 2022) - Alzahrani, Shareefa Ahmed Saleh; Nazreen, Syed; Elhenawy, Ahmed A.; Ahmad, Abrar; Alam, Mohammad Mahboob
Abstract: In the present work, new benzimidazole based 1, 3, 4‐oxadiazole linked thioacetamide conjugates have been synthesized and evaluated for antiproliferative activity. Formation of all the target molecules were elucidated by NMR ( 1 H & 13 C), FTIR, mass spectrometry and other techniques. The compounds displayed significant to moderate cytotoxicity towards MCF‐7, HepG2 and HCT‐116 cancerous cell lines. Among all the compounds, compound 11, 12 and 13 showed promising cytotoxicity with IC50 2.39–10.98 μM, 4.57–16.35 μM and 3.10‐15.58 μM towards MCF‐7, HepG2 and HCT‐116, respectively. Also, compound 11, 12 and 13 inhibited EGFR with IC50 0.91–2.1 μM and exhibited high binding energy of −8.34, −8.06 & −8.08 Kcal/mol, respectively against EGFR protein in docking study. The DFT study was also found to be consistent with the anticancer results of these newly synthesized compounds. It can be concluded that these 1, 3, 4‐oxadiazole based benzimidazole derivatives possess promising anticancer properties and could be used as anticancer leads. Abstract : New 1, 3, 4‐oxadiazole based benzimidazole hybrids were prepared and tested against MCF‐7, HepG2 and HCT‐116 cell lines. Compound 11, 12 and 13 showed promising activity. Also these hybrids inhibited EGFR with IC50 0.91–2.1 μM and exhibited high binding energy against EGFR protein in docking studies.